A CASE REPORT OF MUCINOUS TUBULAR AND SPINDLE CELL CARCINOMA OF THE KIDNEY - Khan, Jawad; Mahmood, Malik Furqan; Muhammad, Ikhtiyar; Abbas, Mudassar; Inam, Fatima (Journal of Ayub Medical College Abbottabad, 2025)
Mucinous Tubular and Spindle Cell Carcinoma (MTSCC) is a rare renal tumour, accounting for 1% of renal tumours. We report a 35-year-old female presenting with right flank pain and a 6.3 cm exophytic hypodense enhancing mass in the upper pole of the right kidney. Histopathology revealed characteristic tubular and spindle cell morphology with mucinous stroma, confirming MTSCC. Surgical resection via partial nephrectomy led to favourable prognosis. This case highlights MTSCC’s distinctive features, diagnostic challenges, and importance of accurate diagnosis for optimal management.